Construction of stretchable supercapacitors using graphene hybrid hydrogels and corrosion-resistant silver nanowire current collectors - Duy, Le Thai; Seo, Hyungtak (Applied Surface Science, 2020)
For wearable electronics applications, developing stretchable materials and energy storages is crucial. Without improving the contact between components of an energy device, maintaining its electrochemical performance during large deformations is challenging. Here, our development of stretchable and chemically stable supercapacitors is introduced using (i) graphene-based hydrogels and (ii) silver-nanowire-based current collector (investing the percolation effect). The stretchable hydrogels are created via a green hydrothermal process using graphene oxide (GO) functionalized with a diol oligomer (enabling stretchability) and PEDOT:PSS (increasing conducitivity and capacitance). Importantly, the stretchable current collector is formed by an alternating sequence of spray-coating silver nanowires (Ag NWs) and GO nanoflakes to not only improve its stability towards elongation and acid corrosion in 0.5 M H3PO4 electrolyte (up to 3 days), but also decrease materials costs (<0.1 USD cm−2). The significance of our supercapacitor electrodes composed of the hydrogels and the current collector with H3PO4 electrolyte is their (i) specific capacitance of 75–108 F g−1 and (ii) notably retention of 70% after a cyclic stretching test (~10000 cycles, 40% elongation) and 60% after an additional cyclic charge-discharge test (3000 cycles). The results suggest that our stretchable hydrogels and corrosion-resistant current collector are promising for developing wearable energy devices.
Keywords: Alternating sequences; Electrochemical performance; Electronics applications; Hydrothermal process; Percolation effects; Specific capacitance; Stretchable materials; Supercapacitor electrodes; Corrosion-resistant; Current collector; Graphene hydrogel; Silver nanowires; Stretchable; Supercapacitors